User satisfaction towards reference librarian behaviours among Bachelor of Science in Information Studies (Hons.) (Library & Information Management) (lM224) in UiTM Kedah / Muhammad Aizat Md Said - Md Said, Muhammad Aizat (2012)
There has been much discussion about the user satisfaction in the library. Research regarding the reference librarian has primarily emphasized the importance of their behaviours required such as approachability, interest, listening/inquiring and follow-up. Those listed are among behaviours required in order to determine user satisfaction. Reference librarians have long been taught and huned skills to assist the patron with the hope that the use oflibrary among students will increase day by day. Actual surveys is taken from the among the final year students of BIS at Universiti Teknologi MARA Kedah which are used to illustrate between the user satisfaction and reference librarian behaviours at Perpustakaan Sultan Badlishah.